THE EFFECT OF PRINCIPAL’S SPIRITUAL LEADERSHIP DIMENSION ON TEACHER AFFECTIVE COMMITMENT - Hafid Aditya Pradesa; Hasrudy Tanjung (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
In managing educational organizations, the role of the principal is vital to support the organization's performance. In high school, the principal's leadership role is used as an essential determinant in building the commitment of teachers in the institution. The purpose of this study was to examine the concept of spiritual leadership from the principal on the affective commitment of the teacher. It is essential to review how attached the teacher is to his organization and how each aspect of spiritual leadership is; vision, hope/faith, and selfless love. By using a quantitative approach in solving this problem, the non-probability sampling method was used in this study and made the teacher the unit of analysis. Forty-eight teachers from Islamic Junior High School in Medan City participated in this study. The results show that among the three aspects of spiritual leadership, hope/faith is found to have the most outstanding value in influencing teachers' affective commitment. Meanwhile, the vision was found to have no significant effect on teachers' affective commitment at Islamic Senior High Schools in Medan City. The findings of this study are discussed further as a basis for further research.